Emotional Encounters and Young Feminine Choreographies in the Helsinki Metro. Issue 1 (1st March 2020) - Mulari, Heta
Abstract: In this article I discuss girls' and non-binary young people's experiences of unwelcome intergenerational encounters in the Helsinki metro underground transport network. I foreground a theoretical conception of the metro as an urban space in which the material is deeply intertwined with the political and as a space with its own racialized, gendered, and age-based hierarchies. Calling on the work of Sara Ahmed, I investigate how girls and non-binary young people make meaning of unwanted emotional encounters in the metro space and how they use and adopt certain material and digital strategies that Helena Saarikoski calls young feminine choreographies, to cope in these situations. This article is based on interviews with girls and non-binary young people who were then between 16 and 17 years of age.